2020
DOI: 10.3390/biom10030493
|View full text |Cite
|
Sign up to set email alerts
|

The Vitamin D Receptor Regulates Glycerolipid and Phospholipid Metabolism in Human Hepatocytes

Abstract: The vitamin D receptor (VDR) must be relevant to liver lipid metabolism because VDR deficient mice are protected from hepatosteatosis. Therefore, our objective was to define the role of VDR on the overall lipid metabolism in human hepatocytes. We developed an adenoviral vector for human VDR and performed transcriptomic and metabolomic analyses of cultured human hepatocytes upon VDR activation by vitamin D (VitD). Twenty percent of the VDR responsive genes were related to lipid metabolism, including MOGAT1, LPG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Additionally, they performed a transcriptomic analysis revealing that one fifth of the VDR responsive genes were related to lipidic pathways such as glycerolipid- and phospholipid metabolism or the uptake of fatty acids. In line with this, they reported a coordinated gene response of these genes due to VDR activation by calcitriol [ 14 ]. Moreover, we found the expression of genes known to play a role in lipid metabolism altered under mild to moderate vitamin D deficiency in a previous study [ 8 ].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Additionally, they performed a transcriptomic analysis revealing that one fifth of the VDR responsive genes were related to lipidic pathways such as glycerolipid- and phospholipid metabolism or the uptake of fatty acids. In line with this, they reported a coordinated gene response of these genes due to VDR activation by calcitriol [ 14 ]. Moreover, we found the expression of genes known to play a role in lipid metabolism altered under mild to moderate vitamin D deficiency in a previous study [ 8 ].…”
Section: Discussionmentioning
confidence: 73%
“…Recent studies provide growing evidence for an important role of vitamin D 3 in the regulation of the lipid homeostasis [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Most of the available studies analyzed this suggested link in the gastrointestinal system, kidney cells or tissue, but we lack information on such an association of vitamin D 3 and lipid metabolism in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many host genes are involved in important stages of the HBV lifecycle, such as viral particle assembly and secretion ( 5 ). Vitamin D and its target receptors have been previously shown to extensively alter the cellular transcriptome and regulate numerous cellular processes ( 59 ). Vitamin D may affect crucial host genes involved in the HBV lifecycle.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that VDR in hepatocytes might play a role in inhibiting bile acid synthesis, thus protecting liver from injury in cholestasis[ 47 ]. Transcriptomic and metabolomic analyses of hepatocytes transfected with human VDR have revealed that 20% of the VDR responsive genes were related to metabolism of lipids (including glycerolipids and phospholipids), uptake of fatty acids, betaine, and glycerol, suggesting a critical role of VDR in lipid metabolism in cultured hepatocytes[ 63 - 65 ]. In a global VDR-deficient mouse model, the livers were protected from steatosis, suggesting that VDR-mediated processes may contribute to NAFLD development[ 66 ], either due to enhanced lipid synthesis or reduced lipid turnover, or both.…”
Section: Differential Vdr Activation In Subsets Of Liver Cellsmentioning
confidence: 99%